Management of mealybugs (Phanacoccus solenopsis) in rainfed cotton (Gossypium hirsutum) - BHOSLE, B B; SHARMA, O P; MORE, D G; BHEDE, B V; BAMBAWALE, O M (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during rainy (kharif) season of 2008 on the incidence of mealybugs rainfed cotton growing areas of Marathwada region in different transgenic cotton hybrids, especially the Phenacoccus solenopsis its the. Severity of incidence was maximum in Parbhani with 40.95% leaf infestations and 35.77% of green boll damage. Lowest incidence was recorded in Hingoli district with 11.37% leaf infestations and 10.10% of green boll damage. Since farmers were using a number of pesticides, field evaluation was carried out at the field of Sategaon Talak. Palam Dist. Parbhani. Out of 12 insecticides tried as curative spray at 2, 7 and 14 days after economic thrush hold level indicates that acephate 70 SP, followed by profenophos 50 EC and diclorvos 76 EC was effective in management of mealybug. The yield of seed cotton was significantly highest in acephate 70 SP (2.22 tonnes/ha) except profenophos 50 EC (2.22 tonnes/ha) which were at par with each other. Â